EVALUASI PROGRAM MAHASISWA KAMPUS MENGAJAR 5 DAN DAMPAKNYA TERHADAP BUDAYA LITERASI DI SEKOLAH MITRA - Azizah, Aurora; Trimurtini; Teguh Supriyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The challenges of innovation and development in education require collaborative effort between the government, educational institutions, teachers, students, and the wider community to ensure education can meet the demands of the industrial era 4.0. This study aims to evaluate the Kampus Mengajar 5 student program and impact of literacy culture in partner school. This research uses the Goal Oriented Evaluation Model with mixed methods. Quantitative data collected through questionnaries involving tutor teachers, school principals, and field supervisors as well as documentation of the results of the Minimum Competency Assessment (AKM) class. Qualitative data were collected through interviews. This research was analyzed with descriptive statistics. The result showed 89,84% and Kampus Mengajar 5 student program was sustainable and had a positive impact on literacy culture in partner school. The Kampus Mengajar 5 student program can prove and has suitability and an important role to support the industrial era 4.0.